Permittivity of ice at radio frequencies: Part I. Coaxial transmission line cell - Bohleber, Pascal; Wagner, Norman; Eisen, Olaf (Cold regions science and technology, 2012)
At radio-frequencies, measurements of the permittivity of ice are sparse and with unknown or large uncertainty. Coaxial transmission lines have been established for frequency-dependent permittivity determination for a broad variety of materials. Here we present a coaxial transmission line setup originally designed for soil samples, now adapted for measuring ice samples between 10MHz and 1.5GHz. Measured scattering parameters are assessed for artifacts against a forward calculation based on transmission line theory. A Debye-type relaxation function for the complex permittivity is assumed to obtain the permittivity of ice from the measured full set of four scattering parameters by means of a genetic optimization algorithm. The algorithm is successfully validated against quasi-analytical and iterative computation techniques with reference measurements of a low-loss Teflon standard. Based on the forward calculation and the Teflon standard, the total uncertainty for measuring the real part of the permittivity is estimated to be around 1%. Additional measurements of reference materials air, water, ethanol and methanol are used for validation. The real part of the permittivity of eight artificial pure ice samples is found frequency-independent between 10MHz and 1.5GHz at −20°C, with a mean value of 3.18±0.01.